(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article scientifically analyzes the historical origin, structure, role of the rubob instrument in traditional and modern performance. Rubob’s importance in the cultural heritage of Uzbekistan, his function in the art of status, as well as his promotion internationally are currently covered. Also, through the teacher-disciple tradition, the continuation of rubob performance and its role in the work of modern composers have been analyzed. The article is intended for musicologists, art historians and researchers interested in National Instruments.